Real-Life Efficacy and Safety of Glecaprevir/Pibrentasvir Pediatric Formulation for Chronic Hepatitis C Infection in Children Aged 3 to 12 Years: A Case Series of 6 Patients - Musto, Francesca; Stracuzzi, Marta; Cibarelli, Alessandro; Coppola, Crescenzo; Caiazzo, Roberta; David, Daniela; Di Tonno, Raffaella; Garcia, Marc Lorenzo; Valentino, Maria Sole; Giacomet, Vania (Clinical therapeutics, 2025)
•Optimal real-life efficacy of glecaprevir/pibrentasvir pediatric formulation for chronic Hepatitis C infection in children aged 3 to 12 years.•Real-life palatability and compliance of glecaprevir/pibrentasvir pediatric formulation.•Good safety of glecaprevir/pibrentasvir pediatric formulation.•Consideration about reducing time of treatment in patients with low viral load. Glecaprevir/pibrentasvir (GLE/PIB) has been approved by the European Medicines Agency and by US Food and Drug Administration for the treatment of children and adolescents aged 3 to 12 years with chronic hepatitis C (CHC) virus infection. The aim of this study was to confirm the real-world effectiveness and safety of GLE/PIB pediatric formulations in children aged 3 to 12 years with CHC. This case series describes a pediatric population (3 to ≤12 years of age) treated with a weight-based dose of GLE/PIB pediatric formulation once daily for 8 weeks. The effectiveness end point was a sustained virologic response 12 weeks after the end of treatment. Safety was assessed on adverse events and clinical/laboratory data. Six patients (median age 6 years; interquartile range, 3 years) were enrolled and treated between March 2023 and December 2023. Genotype distribution was as follows: 4 of 6 genotype 1 (60%), 1 of 6 genotype 2 (20%), and 1 of 6 genotype 3 (20%). Median viral load at baseline was 541,000 IU/mL (interquartile range, 641,000 IU/mL). All (100%) patients completed treatment. Sustained virologic response (SVR) 12 weeks after the end of treatment was 100%. No virologic relapse or breakthrough was observed. No adverse events occurred. This study confirmed the real-life effectiveness and safety profile of an 8-week treatment with GLE/PIB for CHC in children aged 3 to 12 years.